Construction of an artificial zinc alloy layer toward stable zinc-metal anode - Long Jiang; Yizhao Chai; Dongdong Ji; Liwei Li; Le Li; Bingan Lu; Dongmin Li; Jiang Zhou (Green Energy & Environment)
Aqueous zinc-ion batteries (AZIBs) present a promising option for next-generation batteries given their high safety, eco-friendliness, and resource sustainability. Nonetheless, the practical application of zinc anodes is hindered by inevitable parasitic reactions and dendrite growth. Here, zinc alloy layers (i.e., ZnCo and ZnFe alloys) were rationally constructed on the zinc surface by chemical displacement reactions. The alloying process exposes more (002) planes of the ZnCo anode to guide the preferential and dendrite-free zinc deposition. Furthermore, the ZnCo alloy layer not only effectively inhibits water-induced side reactions but also accelerates electrode kinetics, enabling highly reversible zinc plating/stripping. As a result, the ZnCo anode achieves a Coulombic efficiency of 99.2% over 1300 cycles, and the ZnCo symmetric cell exhibits a long cycle life of over 2000 h at 4.4 mA cm−2. Importantly, the ZnCo//NH4V4O10 full cell retains a high discharge capacity of 218.4 mAh g−1 after 800 cycles. Meanwhile, the ZnFe-based symmetric cell also displays excellent cycling stability over 2500 h at 1.77 mA cm−2. This strategy provides a facile anode modification approach toward high-performance AZIBs.